2018
DOI: 10.1038/s41388-018-0177-4
|View full text |Cite
|
Sign up to set email alerts
|

Depression promotes prostate cancer invasion and metastasis via a sympathetic-cAMP-FAK signaling pathway

Abstract: Depression drives cancer progression and induces poor clinical outcome. However, the mechanisms underlying depression and cancer outcomes are unclear. In this work, we investigated 98 prostate cancer patients and found that patients with high score of psychological depression were correlated with tumor invasion and metastasis. We found focal adhesion kinase (FAK) was increased in cancer patients with metastatic features and high score of depression. FAK knockdown completely blocked depression-promoted tumor in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 56 publications
0
48
0
Order By: Relevance
“…To further observe the relationship between the target circRNA and OSCC development, we conducted KEGG pathway analysis using sequencing data and bioinformatics technology. Pathway analysis results showed that many items corresponded to cancer, such as the cAMP signaling pathway, proteoglycans in cancer, and the AMPK signaling pathway [24][25][26][27]. The AMPK pathway has been found to be related to OSCC progression [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To further observe the relationship between the target circRNA and OSCC development, we conducted KEGG pathway analysis using sequencing data and bioinformatics technology. Pathway analysis results showed that many items corresponded to cancer, such as the cAMP signaling pathway, proteoglycans in cancer, and the AMPK signaling pathway [24][25][26][27]. The AMPK pathway has been found to be related to OSCC progression [28].…”
Section: Discussionmentioning
confidence: 99%
“…KEGG results suggested that the top 20 of KEGG enrichment terms are correlated with cancer development (Figure 6A, 6B). Among these items, were tumor-correlated, such as the cAMP signaling pathway, proteoglycans in cancer, and the AMPK signaling pathway [24][25][26][27]. Furthermore, AMPK signaling pathway has been discovered to be correlated with OSCC progression [28].…”
Section: Functional Enrichment Analyses Of Hsa_circ_0086414 Gene and mentioning
confidence: 99%
“…S4C, the fourth cell pathway under 2 μM ADT-OH treatment is cell adhesion. It is well known that the FAK signaling pathway plays a crucial role in the metastasis and invasion of a variety of tumor cells (20)(21)(22). Here, we found that FAK is involved in multiple signaling pathways including cell migration following ADT-OH treatment ( Fig.…”
Section: Adt-oh Inhibits Cell Migration By Regulating Fak Signaling Pmentioning
confidence: 57%
“…We thus inferred that high cAMP levels increase MOB2 expression in GBM cells, resulting in more MOB2 binding to PKA and subsequent enhanced PKA activation, whereas low cAMP levels achieve opposite effects. As the cAMP/PKA signaling is known to inhibit cell migration and invasion [26][27][28][29][30] , we suggest cAMP level-regulated MOB2 as a novel regulator in cAMP/PKA signaling-mediated effects on GBM cell migration and invasion.…”
Section: Discussionmentioning
confidence: 84%
“…The cAMP/PKA signaling has been shown to suppress cell migration and invasion 25 , which involves the inactivation of FAK/Akt [26][27][28][29][30] . We further examined whether FSK affects the activation of FAK/Akt in LN-229 and T98G cells stably depleted MOB2 with two distinct shRNAs.…”
Section: Mob2 Plays a Role In Camp/pka-mediated Inhibition Of Cell MImentioning
confidence: 99%